Political and military relations between the countries of Andalusia and the country of Hijaz between the seventh and ninth centuries AH / the thirteenth and fifteenth centuries AD - Hobi, Eman; Khabut, Sabah (Al-Adab Journal, 2024)
The pilgrimage to the holy lands in the country of the Hijaz is one of the most beloved things for the Muslim man because of its spiritual, psychological and religious influence that brings him closer to God Almighty, despite the difficulties and challenges represented by the distance and political turmoil at the level of the Islamic world and its challenges with the aggressors and the ongoing wars, in Andalusia this matter was considered And starting from the fifth century AH / eleventh century AD, it was very difficult because of the crisis political situation in the Islamic world at that time.